Tagging of Endogenous BK Channels with a Fluorogen-Activating Peptide Reveals β4-Mediated Control of Channel Clustering in Cerebellum - Pratt, Christopher P.; Kuljis, Dika A.; Homanics, Gregg E.; He, Jianjun; Kolodieznyi, Dmytro; Dudem, Srikanth; Hollywood, Mark A.; Barth, Alison L.; Bruchez, Marcel P. (Frontiers in Cellular Neuroscience, 2017)
BK channels are critical regulators of neuronal activity, controlling firing, neurotransmitter release, cerebellar function, and BK channel mutations have been linked to seizure disorders. Modulation of BK channel gating is well characterized, regulated by accessory subunit interactions, intracellular signaling pathways, and membrane potential. In contrast, the role of intracellular trafficking mechanisms in controlling BK channel function, especially in live cells, has been less studied. Fluorogen activating peptides (FAPs) are well-suited for trafficking and physiological studies due to the binding of malachite green (MG) based dyes with sub-nanomolar affinity to the FAP, resulting in bright, photostable, far-red fluorescence. Cell-excluded MG dyes enable the selective tagging of surface protein and tracking through endocytic pathways. We used CRISPR to insert the FAP at the extracellular N-terminus of BKα in the first exon of its native locus, enabling regulation by the native promoter elements and tag incorporation into multiple splice isoforms. Motor coordination was found to be normal; however BK channel expression seems to be reduced in some locations. Alternate start site selection or post-translational proteolytic processing resulted in incomplete FAP tagging of the BKα proteins in brain tissues. In Purkinje cell somata, FAP revealed BK channel clustering previously only observed by electron microscopy. Measurement of these clusters in β4+/- and β4-/- mice showed that puncta number and cluster fluorescence intensity on the soma are reduced in β4-/- knockout animals. This novel mouse line provides a versatile fluorescent platform for studying endogenous BK channels in living and fixed tissues. Future studies could apply this line to ex vivo neuronal cultures to study live-cell channel trafficking.